The effects of dietary boron compounds in supplemented diet on hormonal activity and some biochemical parameters in rats. (March 2015) - Kucukkurt, Ismail; Akbel, Erten; Karabag, Funda; Ince, Sinan
The aims of this study were to clarify the effects of dietary boric acid or borax, as a boron (B) source, on hormonal status (leptin, insulin, triiodothyronine (T3 ), and thyroxine) and some biochemical parameter levels as glucose, carnitine, nonesterified fatty acids, and betahydroxybutyric acid in rats. A total of 30 Sprague-Dawley male rats were divided into three equal groups: the animals in the first group (control) were fed with a standard rodent diet containing 6.4 mg B/kg, and the animals in the experimental group were fed with a standard rodent diet added with boric acid and borax (100 mg B/kg) throughout the experimental period of 28 days. The B compounds especially borax decreased leptin, insulin, and glucose levels, whereas increased T3 and carnitine levels in plasma. In addition, body weight of rats was found to be low in the boric acid group at the end of 4 weeks. Consequently, our results demonstrate that B supplementation (100 mg/kg) in diet decreases body weight, leptin, and insulin, whereas increases T3 levels in plasma, so enhances the metabolic activity of rats. Between the B compounds used in this study, it was found that borax had a greater effect on hormonal status than boric acid.